“Ají Molido” and the municipal elections of 1966 - Garcia Gómez, Christian (2023)
Since 1957, Caretas has published the section “Ají Molido” by Arequipa-born artist Guillermo Osorio Oviedo, who satirized the different Peruvian political problems and tensions through his caricatures. The section ended in October 1968 and covered a large part of the second government of Manuel Prado (1956-1962), as well as the general elections of 1962 and 1963 and the first government of Fernando Belaúnde Terry (1963-1968). Thus, within the framework of the electoral reforms proposed by Belaúnde, municipal elections were reintroduced, which gave rise to two such elections during his administration: the first in 1963 and the second in 1966. In this article, we will focus on analyzing the formal and iconographic resources used by Guillermo Osorio in the caricatures made in the electoral context of 1966, creating a campaign against the candidacy of Jorge Grieve Madge.